2014
DOI: 10.1016/j.ydbio.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Phantom, a cytochrome P450 enzyme essential for ecdysone biosynthesis, plays a critical role in the control of border cell migration in Drosophila

Abstract: Summary The border cells of Drosophila are a model system for coordinated cell migration. Ecdysone signaling has been shown to act as the timing signal to initiate the migration process. Here we find that mutations in phantom (phm), encoding an enzyme in the ecdysone biosynthesis pathway, block border cell migration when the entire follicular epithelium of an egg chamber is mutant, even when the associated germline cells (nurse cells and oocyte) are wildtype. Conversely, mutant germline cells survive and do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 58 publications
4
28
0
Order By: Relevance
“…This hypothesis is consistent with the finding that the ligand sensor for ecdysteroids shows a stage-specific activity including stage 10 and stage 14 (32,33). This notion is further supported by this study that up-regulation of Shd in mature follicle cells produces 20E to regulate ovulation and a previous study that local ecdysteroids produced in follicle cells regulate border cell migration (37).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This hypothesis is consistent with the finding that the ligand sensor for ecdysteroids shows a stage-specific activity including stage 10 and stage 14 (32,33). This notion is further supported by this study that up-regulation of Shd in mature follicle cells produces 20E to regulate ovulation and a previous study that local ecdysteroids produced in follicle cells regulate border cell migration (37).…”
Section: Discussionsupporting
confidence: 93%
“…Ecdysteroids have long been known to play essential roles in developmental transitions, such as larval molting and metamorphosis (27,28). In contrast, the roles of ecdysteroids in adult physiology have just started to emerge (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…EcR and downstream components of the ecdysone-signaling pathway are genetically required for oocyte development [23][24][25]. Moreover, a recent study has shown that ecdysone produced from the somatic follicle cells is required for border cell migration during stage 9 of oogenesis [26]. However, the importance of EcR in nutrient storage during late stages of egg development has not been defined.…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition, certain genes encoding the ecdysteroidogenic enzymes are required for egg development after stage 8, 19,26 egg production, 30 and border cell migration. 31 It is well-documented that, for the regulation of molting and metamorphosis, the biosynthesis and signaling of ecdysteroids are coordinately modulated in response to various environmental cues such as nutrition, photoperiod, and temperature. 32,33 Therefore, it is possible that the environmental cues are also reflected in egg production processes such as in the control of GSC number.…”
Section: Introductionmentioning
confidence: 99%